Synthesis, characterization, spectral studies, and antifungal activity of Mn(II), Fe(II), Co(II), Ni(II), Cu(II), and Zn(II) complexes with 2-hydroxy-1-(1-hydroxy-2-naphthylazo)-6-nitronaphthalene-4-sulfonic acid sodium salt - Pandey G.; Narang K.K. (My University, 2025)
Mn(II), Fe(II), Co(II), Ni(II), Cu(II), and Zn(II), complexes of the type Na2[M(HL)2(H2O)2] of the ligand 2-hydroxy-1-(1-hydroxy-2-naphthylazo)-6-nitronaphthalene-4-sulfonic acid sodium salt (Eriochrome Black T, NaH2L), have been synthesized and characterized by various physicochemical (elemental analyzes, solubility, electrolytic conductances and magnetic susceptibility measurements) and spectral (UV-Visible spectra, IR spectra, ESR spectra, and powder x-ray diffraction) techniques for the structure determination and the antifungal activity was measured against 10 fungi. The data suggest 1:2 (M:L) compositions with octahedral geometries around M(II), except for Cu(II), very significant antifungal activity against Alternaria brassicicola and Alternaria brassicae and moderate activity against the fungi Alternaria solanae, Curvularia species, Curvularia lunata, Helminthosporium oryzae, Collectotrichum capsici, Aspergillus niger, Aspergillus flavus, and Fusarium udum.